Aggregated Pt–Pd nanoparticles on Nafion membrane for impulsive decomposition of hydrogen peroxide1. Issue 57 (25th June 2015) - Hasnat, Mohammad A.; Rahman, Mohammed M.; Siddiquey, Iqbal A.; Borhanuddin, S. M.; Alam, M. Saiful; Rahman, M. Hamidur; Asiri, Abdullah M.
<x xml:space="preserve">Abstract</x> A Pd site initiates hydrogen peroxide decomposition by adsorbing one 'O' followed by splitting of O–H bond. Meanwhile, a Pt site finally completes the decomposition process by enabling desorption of the incipient O2 species.